Factors favoring pregnancy continuation among women hospitalized due to miscarriage threat - Płoch, Kazimiera; Dziedzic, Małgorzata; Matuszyk, Dorota; Frączek, Ewelina (Nursing in the 21st Century, 2015)
FACTORS FAVORING PREGNANCY CONTINUATION AMONG WOMEN HOSPITALIZED DUE TO MISCARRIAGE THREATIntroduction. Miscarriage is a serious medical, social and family problem. It is defined as a premature pregnancy termination before 22nd week and it relates to about 10-15% of recognized pregnancies. Its symptoms usually include painless bleeding from uterus and medium force contraction. With preservative treatment the symptoms disappear and the pregnancy continues to the correct termination. Possible termination methods are limited by potential threats to pregnancy. Chances for success are very high, as long as professional medical assistance is provided.Aim. Determination of the relationship between socio-demographic factors and the factors accompanying treatment for pregnancy subsistence among women hospitalized due to miscarriage threat.Material and Methodology. Medical documentation of 145 pregnant women hospitalized due to miscarriage threat in Radom Specialist Hospital between January and March 2014. Statistical analysis was performed with Statistica 10 PL software. Confidence level was assumed at p≤0.05.Results. T Hospitalization and medical treatment effectiveness for pregnancy subsistence was at 87.6 %. It was statistically proven that the highest impact was exercised by medications applied (p=0.000), bed regime (p=0.040) and a week of pregnancy continuation. Its continuation between 8-16 weeks proved to be the most favorable from among examined pregnant women with threatened pregnancies, for its subsistence (p=0.014).Conclusion. Pharmacotherapy and rest therapy used during hospitalization had favorable influence upon pregnancy subsistence. There was a positive correlation between pregnancy subsistence, folic acid supplementation, correct BMI and the week when miscarriage occurred. No other examined parameters had any impact on pregnancy subsistence in the researched population whatsoever.